Improving students’ interest in learning simple past tense using teams games tournaments - Yusnita Yusnita; Yuniarti Yuniarti (UPT Bahasa Universitas Tanjungpura, 2020)
This study aims to describe the students’ interests and perceptions in learning simple past tense by using the TGT (Team Game Tournament) technique. The situation in the teaching-learning process at an Islamic Junior High School in Pontianak has shown that there are still many problems that must be addressed, concerning English grammar. The researcher has encountered several problems such as student’s reluctance to participate, lack of interest, motivation, and attention in the classroom. The researcher employed Classroom Action Research as a means to solve the problems. The findings presented information regarding the use of TGT that could serve as a beneficial alternative in teaching grammar, particularly the simple past tense. Furthermore, the information will provide the teacher with useful insights on ways to teach and to motivate their students in the classroom.